A new cryptic species of glassfrog (Centrolenidae: Nymphargus) from Reserva Las Gralarias, Ecuador - Hutter, Carl R.; Guayasamin, Juan M. (Zootaxa, 2012)
We describe a new species of Nymphargus from Reserva Las Gralarias, in the montane forests of the Pacific versant ofthe Andes of Ecuador. The new species, Nymphargus lasgralarias sp. nov., is nearly morphologically identical to sym-patric Nymphargus griffithsi (Goin 1961), with the exception of the following characters: (i) a gold colored iris with nu-merous small spots and lighter reticulation, (ii) absence of dark dorsal spotting, and (iii) a significantly larger body size.Additionally, we describe the vocalizations for N. griffithsi and N. lasgralarias. The call of N. lasgralarias sp. nov. is eas-ily distinguished from N. griffithsi through the following temporal and spectral characteristics: (i) calls are emitted in series, (ii) waveform shape is always pulsed, (iii) significantly shorter call duration, and (iv) lower dominant frequency.